Underinsurance Among Children in the United States - Yu, Justin; Perrin, James M; Hagerman, Thomas; Houtrow, Amy J (Pediatrics (Evanston), 2022)
We describe the change in the percentage of children lacking continuous and adequate health insurance (underinsurance) from 2016 to 2019. We also examine the relationships between child health complexity and insurance type with underinsurance. Secondary analysis of US children in the National Survey of Children's Health combined 2016-2019 dataset who had continuous and adequate health insurance. We calculated differences in point estimates, with 95% confidence intervals (CIs), to describe changes in our outcomes over the study period. We used multivariable logistic regression adjusted for sociodemographic characteristics and examined relationships between child health complexity and insurance type with underinsurance. From 2016 to 2019, the proportion of US children experiencing underinsurance rose from 30.6% to 34.0% (+3.4%; 95% CI, +1.9% to +4.9%), an additional 2.4 million children. This trend was driven by rising insurance inadequacy (24.8% to 27.9% [+3.1%; 95% CI, +1.7% to +4.5%]), which was mainly experienced as unreasonable out-of-pocket medical expenses. Although the estimate of children lacking continuous insurance coverage rose from 8.1% to 8.7% (+0.6%), it was not significant at the 95% CI (-0.5% to +1.7%). We observed significant growth in underinsurance among White and multiracial children, children living in households with income ≥200% of the federal poverty limit, and those with private health insurance. Increased child health complexity and private insurance were significantly associated with experiencing underinsurance (adjusted odds ratio, 1.9 and 3.5, respectively). Underinsurance is increasing among US children because of rising inadequacy. Reforms to the child health insurance system are necessary to curb this problem.